Elaboração de melomel de cupuaçu (Theobroma grandiflorum Schumann) com mel de abelhas-sem-ferrão da Amazônia - Rocha, Helen Maria Silva da (Brasil, 2025)
Mead is a beverage obtained by the fermentation of honey, yeast and water, with an alcohol content of 4 to 14%. When the must is added with fruits, the resulting beverage is called melomel. The objective of this study was to develop the production process of cupuaçu melomel with honey from stingless bees (ASF) native to the Amazon. For the fermentation of the must, 1300 g of cupuaçu pulp, jandaíra honey (Melipona sp.) in an amount that reached 20 °Brix, together with 1 g of the yeast Shaccharomyces cerevisiae (M05) and 1 g of each Saccharomyces bayanus (Red Star Premier Blanc and Red Star Premier Cotê des Blancs), previously hydrated, were mixed. A total of 6 L of must were produced, which were divided into three parts and kept in containers with a capacity of 2 L each, containing an airlock valve. Fermentation was monitored daily until total soluble solids were constant. After bottling, the beverages were analyzed for physical-chemical parameters of alcohol content, total soluble solids, total acidity and pH. Fermentation monitoring showed that the results achieved are in accordance with Normative Instruction No. 34 of November 2012, which defines quality limits for mead production, presenting the results found for alcohol content (11.9%; 11.7%; 12.5%), total soluble solids (7; 7.2; 6 °Brix), total acidity (50 mEq/L; 50mEq/L; 50mEq/L) and pH (3.5; 3.5; 3.5) for the three types of formulations prepared. Acceptability and purchase attitude tests were performed for the attributes appearance, aroma, flavor, texture and overall impression of the samples. There was no difference in sensory attributes regarding the variations in the melomel formulations; the average values obtained were between 5.86 (appearance), 5.22 (flavor), 5.90 (texture), aroma (5.66) and overall impression (5.98) for the different formulations. The purchase intention questionnaire indicates that formulations A and C had a higher probability of “probably would buy” and formulation B had a higher rejection for “probably would not buy”, with it being observed that the formulations that contained higher concentrations of pulp had a higher chance of being purchased. In general, the production of cupuaçu melomel with honey from stingless bees from the Amazon proved to be efficient, adding value to the Amazonian raw materials.